Biofilm formation by multidrug resistant Escherichia coli ST131 is dependent on type 1 fimbriae and assay conditions. Issue 3 (2nd March 2016) - Sarkar, Sohinee; Vagenas, Dimitrios; Schembri, Mark A.; Totsika, Makrina
Abstract : Escherichia coli sequence type 131 (ST131) has emerged as a pandemic lineage of important multidrug resistant pathogens worldwide. Despite many studies examining the epidemiology of ST131, only a few studies to date have investigated the capacity of ST131 strains to form biofilms. Some of these studies have reported contrasting findings, with no specific ST131 biofilm-promoting factors identified. Here, we examined a diverse collection of ST131 isolates for in vitro biofilm formation in different media and assay conditions, including urine from healthy adult women. We found significant differences among strains and assay conditions, which offers an explanation for the contrasting findings reported by previous studies using a single condition. Importantly, we showed that expression of type 1 fimbriae is a critical determinant for biofilm formation by ST131 strains and that inhibition of the FimH adhesin significantly reduces biofilm formation. We also offer direct genetic evidence for the contribution of type 1 fimbriae in biofilm formation by the reference ST131 strain EC958, a representative of the clinically dominant H 30-Rx ST131 subgroup. This is the first study of ST131 biofilm formation in biologically relevant conditions and paves the way for the application of FimH inhibitors in treating drug resistant ST131 biofilm infections. Abstract : This study investigated biofilm formation by the globally disseminated multidrug resistant Escherichia coli ST131 in biologically relevant conditions and identified the first critical biofilm promoting factor in this lineage.